Oxford economic papers. (Oxford : Oxford University Press, 1938)
Oxford Economic Papers is a general economics journal, publishing refereed papers in economic theory, applied economics, econometrics, economic development, economic history, and the history of economic thought.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Economics -- Periodicals